2023
DOI: 10.1021/acs.joc.3c00646
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical and Single Electron Transfer Generation of 2′-Deoxycytidin-N4-yl Radical from Oxime Esters

Haihui Peng,
Son Vu,
Parker Retes
et al.

Abstract: A 2′-deoxycytidin-N4-yl radical (dC•), a strong oxidant that also abstracts hydrogen atoms from carbon−hydrogen bonds, is produced in a variety of DNA damaging processes. We describe here the independent generation of dC• from oxime esters under UV-irradiation or single electron transfer conditions. Support for this σ-type iminyl radical generation is provided by product studies carried out under aerobic and anaerobic conditions, as well as electron spin resonance (ESR) characterization of dC• in a homogeneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Photolysis studies also revealed 88 can recombine with the aryloxyl radical to regenerate 87, undergo C5-C6 addition to produce diradicals, generate deoxycytidine via reduction, or react under aerobic conditions to generate other radicals/products. Iminyl radical 88 was also independently generated (and characterized by EPR) via single-electron transfer to oxime ester 89 [110]. Like with adeninyl radical 72, tandem lesion formation from cytosinyl radical 88 is traceless because it is reduced to dC during the process.…”
Section: Nitrogen-centered Radicals Generated On Non-azido Nucleobasesmentioning
confidence: 99%
See 2 more Smart Citations
“…Photolysis studies also revealed 88 can recombine with the aryloxyl radical to regenerate 87, undergo C5-C6 addition to produce diradicals, generate deoxycytidine via reduction, or react under aerobic conditions to generate other radicals/products. Iminyl radical 88 was also independently generated (and characterized by EPR) via single-electron transfer to oxime ester 89 [110]. Like with adeninyl radical 72, tandem lesion formation from cytosinyl radical 88 is traceless because it is reduced to dC during the process.…”
Section: Nitrogen-centered Radicals Generated On Non-azido Nucleobasesmentioning
confidence: 99%
“…The tautomerization of syn-aminyl radical also leads to the iminyl σ-radical 88 [111,112]. Interestingly, contrary to these findings, [109][110][111] the one-electron reduction (conditions for DEA) of azide precursors at the C4 positions of pyrimidine bases (62 or 63) led to the formation of anion radicals 66 or 67 (see Figure 11) [94,95]. One-electron oxidation and ESR studies of 1-methylcytosine and 2 ′ -deoxycytidine 91 showed that the cytidine cation radical 92 preferentially deprotonates to form an aminyl radical 94 syn to the carbonyl moiety (Figure 17).…”
Section: Nitrogen-centered Radicals Generated On Non-azido Nucleobasesmentioning
confidence: 99%
See 1 more Smart Citation
“…While much progress has been made in this area over the past decade, significant limitations still remain, such as the need for pre-functionalization of substrates, the need for toxic and hazardous reagents, a narrow range of substrates, and drastic reaction conditions. [11] Consequently, there is still a high demand to develop efficient and simple methods for generation of iminyl radicals from readily available starting compounds and their application in the syn-thesis of N-heterocyclic compounds. Of particular interest is the photochemical strategy for generating the iminyl radical from biaryl acyl oximes, which makes it possible to carry out the reaction under mostly mild conditions (room temperature) and without metal catalysts.…”
Section: Introductionmentioning
confidence: 99%